Mandarin Chinese phrase book & dictionary (Berlitz Publishing, 2018)
Berlitz Phrasebook and Dictionary Mandarin Compact, clear, and packed with key words and phrases to helpconversation, this pocket-sized Mandarin phrasebook and dictionary from Berlitz's trusted languageexperts (with free app) isa trusty travel companion, and all you need to make yourself understood - andto understand others - when you're out and about. · With itsemphasis on conversational usage, and up-to-date language on social media,leisure, business - and more - this is the only phrase book you'll need when exploring · Includes 3000-wordbilingual dictionary · Visually appealingcolour-coding system means you can find what you want, when you want, and fast · The simplified Berlitzpronunciation system will ensure you're clearly understood · Stunning colour photographyenhances the expert content, and makes this series the most visually attractivephrase book on the market About Berlitz: Berlitz draws on years of travel and language expertise tobring you a wide range of travel and language products, including travelguides, maps, phrase books, language-learning courses, dictionaries and kids'language products.